A CMOS down-conversion mixer for microwave radar application. Issue 1 (1st November 2022) - Lin, Shaopan; Su, Boming; Chen, Sikai; Wu, Yi; Huang, Guochi
Abstract : This paper introduces a CMOS down-conversion mixer for microwave radar application. The mixer is based on the classical Gilbert cell architecture, using PMOS current bleeding technology and cross-coupling as a transconductance stage to further elevate the conversion gain and decrease the noise factor, while introducing source negative feedback technology to enhance the linearity performance of the mixer. Using the SMIC 0.13 um CMOS process, the simulation results prove that the frequency conversion gain of the mixer is 12.31 dB, the noise factor is 21.16 dB, and the -1dB compression point of the output is -12.66 dBm when the input RF signal is 10 GHz and the output IF signal is 10 MHz. The third-order intermodulation cut-off point is -1.70 dBm, and the power dissipation is 3.16 mW under a 1.2 V power supply.